The Effectiveness Of The National Land Agency In Implementing The Complete Systemic Land Registration Program - Sri Rahayu Mootalu (Universitas Negeri Gorontalo, 2020)
The research aims to determine to what extent the role of Nasional Land Agency in implementing the complete and systematic Land Registration (PTSL) program and internal and external factors inhibiting the National Land Agency in implementing the Complate and Systematic Land Registration (PTSL) program towards the improvement of Land Certificate Ownership Data in Gorontalo Regency. In this case, the program has been done well, yet it remains encountering several problems. The research employs empirical legal research. The problems in this current research are the role of National Land Agency in implementing the Complate and Systematic Land Registration (PTSL) program towards the impprovment of Land Certificate Ownership Data in Gorontalo Regency and internal and external factors inhibiting the implementation of program. The research finding reveals that the implementation of Complete and Systematic Land Registration (PTSL) program by National Land Agency remains not maximum. Therefore, it is necessary to fiind a preper solition so that the PTSL program could achieve the predetermined target and implementation stages must be in accordance with the prevailing regulation. Keywords: Role of BPN, PTSL Program, Land Certificate Ownership